Early time course of major bleeding on antiplatelet therapy after TIA or ischemic stroke - Hilkens, Nina A.; Algra, Ale; Kappelle, L. Jaap; Bath, Philip M.; Csiba, László; Rothwell, Peter M.; Greving, Jacoba P. (American Academy of Neurology, 2018)
Objective: To study the early time course of major bleeding and its subtypes in patients with cerebral ischemia on dual and single antiplatelet therapy.